Here's how to do stuttering therapy - Rentschler, Gary J., 1947- (Here's how series., 2012)
This practical guide to stuttering therapy is based upon a well-articulated philosophy of the disorder. It provides a hands-on, eclectic approach centered on the needs of the client, rather than the structure of any specific treatment program.